ANALISIS PENGGUNAAN KEKUASAAN DAN SUMBER DAYA PUBLIK OLEH PEMERINTAH PROVINSI DKI JAKARTA DALAM PENGENDALIAN PENCEMARAN UDARA DI DKI JAKARTA TAHUN 2003 - Tambun, Anisa Putri; Darmawan, Ivan; Saefulrahman, Iyep (Gorontalo Law Review, 2024)
This research is entitled "Strategy of the DKI Jakarta Provincial Government in Controlling Air Pollution in DKI Jakarta in 2023" and is motivated by the demands of the community for the provision of clean air in DKI Jakarta, but the power (authority) and public resources of the DKI Jakarta Provincial Government have not been maximized to control high levels of air pollution in 2023. Borrowing the definition of "government strategy" by Mulgan (2009), the author uses it as a research analysis tool. The research method used is qualitative with a descriptive analysis type to achieve the research objectives. Data collection was carried out using observation, interview, and documentation techniques. The informants in this research were the Environmental Service, Health Service, DKI Jakarta Provincial Government Air Pollution Control Task Force, Walhi DKI Jakarta, WRII, Bicara Udara, DPD Organda DKI Jakarta, Kadin DKI Jakarta, and the citizens of DKI Jakarta. The research results show that the DKI Jakarta Provincial Government in using its authority is utilizing cross-sectoral performance and even the DKI Jakarta Provincial Government Air Pollution Control Task Force in accordance with the agency's capacity to implement the Air Pollution Control Strategy in accordance with the Decree of the Governor of DKI Jakarta No. 576/2023 and becoming a collaborator for non-government parties in realizing projects to achieve air pollution control goals, such as Clean Air Catalyst. The use of public resources utilizes human resource knowledge, budget, and air pollution control infrastructure facilities. The conclusion of the research shows that there are notes for the implementation of the strategy indicated by the ineffective use of authority because it is still being carried out separatistly, the lack of a picture of air pollution problems as structural problems, the determination of short-term solutions that drain the budget with unclear regulatory bases such as water mist generators, the absence of studies on air pollution sources per administrative city region in DKI Jakarta, and the lack of optimal regulations for protecting the community.